Development of Salted Egg Maker by Using PLC Based on Osmotic Pressure Method - Masfufiah, Ilmiatul; Firmansyah, Vegal; Muharom, Syahri; Firmansyah, Riza Agung; Prabowo, Yulianto Agung; Pambudi, Wahyu Setyo (ELKHA : Jurnal Teknik Elektro, 2024)
Salted egg is one of the egg types that has a lot of devotees because it tastes a little salty and savory. Salted eggs are usually homemade in various regions. The easy process of making them has attracted many people to do so. This study developed a PLC-based on automatic system for a salted egg maker using the osmotic pressure method to accelerate the opening of the semi-permeable membrane on duck eggshells so that the salting mixture seeps into the eggs more quickly. It was carried out in an osmotic pool containing water and acetic acid at a concentration of 5%. The data collection process in designing the salted egg maker consisted of evaluating the performance of photoelectric sensors, proximity sensors, temperature controller, thermostat set point, baking time, and salted egg durability test. The results of the tests indicated that the time needed to make salted eggs from raw eggs to cooked eggs only took 36 minutes using the machine designed. Additionally, the presented salted egg maker reveals the short making time, and long salted egg durability. altogether revealing full potential to be easily used for practical applications.